Chatbot Kantor Pelayanan Pajak Pratama Cikupa pada Platform Line - Mustikaning Sitoresmi; Wella Wella (Universitas Multimedia Nusantara, 2020)
The Primary Tax Service Office has used technology in delivering information about taxes, such as the existence of an official tax portal service site as a forum for delivering information about requirements, announcements and provisions related to taxes for the general public. In addition, there are also online applications that are under the auspices of the Directorate General of Taxation which serve as services related to online tax reporting for the general public. However, the Primary Tax Service Office does not yet have a service to provide services to users quickly, easily and can be used at any time, therefore a chatbot application is created that can answer tax-related questions that can be accessed at any time easily and quickly. This chatbot is built using the hypertext preprocessor programming language and database using MySQL and the Artificial Intelligence Markup Language which contains a collection of patterns and responses that can be used by chatbots to search answers to each sentence. The software development methodology used is the Rapid Application Development (RAD) method. This research produces a chatbot application that can help users by answering questions about taxes.